SIGNing a symbiotic treaty with gut microbiota - Lugo-Villarino, Geanncarlo (EMBO J, 2015)
Beneficial microbes hold great promise for the treatment of a wide range of immune and inflammatory disorders. In this issue of The EMBO Journal, Lightfoot and colleagues report how the food-grade bacterium Lactobacillus acidophilus helps the immune system to limit experimental colitis in mice through interaction between SIGNR3 and surface layer protein A (SlpA) in L. acidophilus. These results pave the way for future development of novel therapies for inflammatory diseases, including inflammatory bowel disease.